Original Articles:Outcomes after resection of occupational cholangiocarcinoma. (1st August 2016) - Kubo, Shoji; Takemura, Shigekazu; Tanaka, Shogo; Shinkawa, Hiroji; Kinoshita, Masahiko; Hamano, Genya; Ito, Tokuji; Koda, Masaki; Aota, Takanori; Yamamoto, Takatsugu; Terajima, Hiroaki; Tachiyama, Gorou; et al.
Abstract: Background: Cholangiocarcinoma caused by exposure to 1, 2‐dichloropropane and/or dichloromethane is recognized as occupational cholangiocarcinoma. The aim of this study was to investigate the outcomes after resection of occupational cholangiocarcinoma to establish a treatment strategy for this disease. Methods: Clinicopathological findings and outcomes after surgical intervention in 20 patients with occupational cholangiocarcinoma were investigated. Results: Of 20 the patients, curative resection was performed in 16 patients. Three patients underwent radiation at the stump of the bile ducts. Adjuvant chemotherapy was performed in 12 patients. Biliary intraepithelial neoplasia, intraductal papillary neoplasm of the bile duct, and/or chronic bile duct injury was detected in most subjects. Intraabdominal infection developed after surgery in nine patients. Cholangiocarcinoma recurred in 12 of the 20 patients. The recurrent tumors in five patients developed at a different part of the bile duct from the primary tumor and a second resection was performed in four of these five patients. Conclusions: The incidence of postoperative complications including intraabdominal infection was high in patients with occupational cholangiocarcinoma. Multicentric recurrence occurred not infrequently after surgery because the bile ducts had a high potential for the development of carcinoma. The aggressive treatment including second resection for the multicentric recurrence appeared to be effective. Abstract : Highlight In patients with occupational cholangiocarcinoma caused by exposure to 1, 2‐dichloropropane, dichloromethane, or both, Kubo and colleagues showed that multicentric recurrence occurred not infrequently after resection of the cholangiocarcinoma because of the high carcinogenic potential of the bile duct. Aggressive treatment including resection for the multicentric recurrence appeared to be effective.